Ecofeminist Movement: Roles of Youth in Community-Based Waste Recycling Management - Rahmayna, Kania Bening (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2024)
This study discusses a social enterprise for sustainable inorganic waste management called Daur Resik in the Special Region of Yogyakarta, Sukoharjo, Solo, and Magelang, developed by young women to solve waste management problems in the community. Daur Resik strengthens education through Trash for School activities and deals with issues of ecological justice and women. This research aims to analyze the role of young people in waste management in the Daur Resik community from an ecofeminist perspective. Qualitative descriptive methods were used in the research through literature review, observation, and in-depth interviews with the founders, front liners, and the community involved in Daur Resik activities in Yogyakarta. The data was analyzed using ecofeminism theory (perspectives of women, young people, children, elderly, and disabled) and sustainable development goals (SDGs). The results indicated that waste management and Recycling Education activities initiated by young people were, in practice, able to inspire communities (especially women, young people, and families) to change their lifestyle to be more environmentally friendly through responsible waste management, donation to public education, and support for the ratification of the TPKS Bill. In the educational process, Daur Resik maximizes social media in collaboration with universities, educational institutions, community organizations, and other feminist groups.